KINERJA BULK-MODIFIED DAN PEDIGREE UNTUK KETAHANAN KEDELAI TERHADAP HAMA PENGHISAP POLONG Riptortus linearis Fabricius (HEMIPTERA: ALYDIDAE) - Yakub, Sahiral; Purwantoro, Azis; Nasrullah, Nasrullah; Asadi, Asadi (JURNAL AGROTROPIKA, 2020)
Pod sucker bug, Riptortus linearis Fabricius. (Hemiptera: Alydidae) is an important insect pest on soybean in Indonesia that caused significantly yield loss. Growing the resistant soybean is a simple method, efficient, and friendly environment to control the insect pest in the field. The aim of the research is to know the performance selection method (bulk-modified and pedigree) for soybean resistance against pod sucker bug. The research was conducted at BB Biogen, Bogor from June up to October 2010 and November 2010 up to March 2011. The genetic material consisted of progenies F3 and F4 population from ‘Tambora’ × B4400 hybridization. A pairs of Riptortus linearis each 20 plant was infested at pod formation up to pod filling period (R3-R4) in each generation. The numbers of pod and seed damage level and soybean yield were used as a resistance indicator against pod sucker bug. The Result showed that F3 and F4 population showed a high phenotypic and genotypic variance and high heritability in a broad sense. Both F3 selected and F4 selected population showed the percentage numbers of pod and seed damage were lower than 20% (resistant), but the yield still lower than both parents. Bulk-modified and pedigree performance were significantly different via realized selection response on soybean characters estimates. Pedigree performance show higher response selection estimates than bulk-modified on pod and seed damage level, but not on yield. Keyword : selection method, response selection, resistant soybean